2020
DOI: 10.2217/cer-2020-0142
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementation of a hysterectomy enhanced recovery pathway on anesthetic medication costs

Abstract: Aim: To evaluate the effect of implementation of a hysterectomy Enhanced Recovery After Surgery (ERAS) protocol on perioperative anesthetic medication costs. Patients & methods: Historical cohort study of 84 adult patients who underwent a hysterectomy. Forty-two patients who underwent surgery before protocol implementation comprised the pre-ERAS group. Forty-two patients who underwent surgery after protocol implementation comprised the post-ERAS group. Data on anesthetic medication costs and outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Total hysterectomy is one of the commonly used gynecological operations. It is often used to treat patients who have poor conservative treatment effects and no fertility requirements due to benign uterine diseases [3][4][5]. In addition, a total hysterectomy is also needed for the treatment of uterine malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Total hysterectomy is one of the commonly used gynecological operations. It is often used to treat patients who have poor conservative treatment effects and no fertility requirements due to benign uterine diseases [3][4][5]. In addition, a total hysterectomy is also needed for the treatment of uterine malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ERP in gynaecological surgery, and more specifically with regard to hysterectomies has been studied for about 10 years. Since 2010, several studies have confirmed a reduction in the length of stay,8–10 the costs of treatment11 12 and the consumption of postoperative opioids13–15 after their implementation. However, patients’ views on their recovery using a recognised medical measurement tool have never been studied as a primary endpoint.…”
Section: Introductionmentioning
confidence: 99%